1977
DOI: 10.1111/j.1752-1688.1977.tb02056.x
|View full text |Cite
|
Sign up to set email alerts
|

AQUATIC TRANSPORT OF HEAVY METALS IN THE URBAN ENVIRONMENT1

Abstract: A study has been conducted for the past two years on a 4.6 mile stretch of the Saddle River near Lodi, New Jersey. The primary objectives of this study were two fold; initially, the amounts of various heavy metals being contributed to the Saddle River by stormwater runoff, rainfall, and individual tributaries, etc., were investigated to better delineate the distribution of various sources of heavy metals to the aquatic environment. Secondly, a series of benthal deposits from the Saddle River were analyzed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…Peak concentrations of lead and phosphorus occurred within 10 min after the start of rainfall. Similar peaks at the onset of runoff have been observed in other studies of urban runoff quality (Wilber and Hunter, 1977;Helsel and others, 1979). The second peak on the suspended-solids hydrograph is reduced approximately 300 mg/1 from the first peak although the peak discharge is nearly the same.…”
Section: Urban Runoffsupporting
confidence: 86%
“…Peak concentrations of lead and phosphorus occurred within 10 min after the start of rainfall. Similar peaks at the onset of runoff have been observed in other studies of urban runoff quality (Wilber and Hunter, 1977;Helsel and others, 1979). The second peak on the suspended-solids hydrograph is reduced approximately 300 mg/1 from the first peak although the peak discharge is nearly the same.…”
Section: Urban Runoffsupporting
confidence: 86%
“…Streams in the piedmont area of North Carolina are particularly susceptible to sediment problems because erodible soils contain a high percentage of clay-sized particles . These smaller particles stay in suspension for long periods of time and may adsorb trace metals (Wilber & Hunter, 1977) . indicated that sediment eroding from clay soil types had a greater affect on stream macroinvertebrates than sediments eroding from sandy soil types .…”
Section: Introductionmentioning
confidence: 99%
“…An increase of some other metals during high water flow and flood was also found in mountain streams (Abesser et al, 2006;Hardie et al, 2007). In such periods, additional sources of metals may be atmospheric precipitation or re-suspension of river sediments, which often act as 'secondary' sources of pollution (Baborowski et al, 2004;Wilber and Hunter, 2007). The contents of Cr and Ni were also dependent on the Biała Tarnowska River flow, indicating diffuse contamination as a dominant source.…”
Section: Discussionmentioning
confidence: 78%